2018
DOI: 10.5152/tjg.2018.18200
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of pain and patient satisfaction by music therapy in patients with endoscopy/colonoscopy

Abstract: The present study may serve as the beginning of using music therapy for pain treatment in gastroenterology procedures in our hospital with/without sedation. Music and other non-pharmacological treatment methods must be remembered to increase patient comfort during enco/colonoscopies and other painful procedures.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
27
3
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(32 citation statements)
references
References 26 publications
0
27
3
2
Order By: Relevance
“…To confirm this data, in the analysis within the single groups between anxiety before procedure and at the end of the procedure, only in the group which underwent the procedure in conscious sedation with music there is a significant difference. This data differs from that of a previous study (Bashiri et al, 2018), where music has an effect also in support of deep sedation. The use of music both in support of conscious sedation and deep sedation leads to a significant reduction in pain according to previous studies (Costa et al, 2010) and as shown in binary logistic model, it is a limiting factor regarding satisfaction and willingness to repeat the procedure under the same conditions.…”
Section: Discussioncontrasting
confidence: 99%
See 3 more Smart Citations
“…To confirm this data, in the analysis within the single groups between anxiety before procedure and at the end of the procedure, only in the group which underwent the procedure in conscious sedation with music there is a significant difference. This data differs from that of a previous study (Bashiri et al, 2018), where music has an effect also in support of deep sedation. The use of music both in support of conscious sedation and deep sedation leads to a significant reduction in pain according to previous studies (Costa et al, 2010) and as shown in binary logistic model, it is a limiting factor regarding satisfaction and willingness to repeat the procedure under the same conditions.…”
Section: Discussioncontrasting
confidence: 99%
“…Music stimulates, also, the endocrine system to secrete more endorphins to reduce pain (Chia-Hui et al, 2017). Our data, unlike previous study (Bashiri et al, 2018) are not applicable in groups with deep sedation where the only significant difference is degree of anxiety at the end of the procedure (96 (15) versus 69 (12) p 4.6E-8).…”
Section: Discussioncontrasting
confidence: 81%
See 2 more Smart Citations
“…Furthermore, a meta-analysis by Martin-Saavedra, Vergara-Mendez, & Talero-Gutiérrez, (2018) found that music intervention delivered as music without lyrics, percussion music, or natural sounds with a melody at a tempo of 60–80 bpm was superior to RC regarding pain relief in 39 trials (3,460 patients; SMD = −0.58; 95%CI: −0.78 to −0.38; p < .01). The age of patients might partly explain the discrepancy (Bashiri et al, 2018; Mandel et al, 2019), since pain perception and threshold vary with age group (Lautenbacher, Peters, Heesen, Scheel, & Kunz, 2017). Moreover, the music intervention (the person responsible for selection, volume, music type, listening tool, duration, and intervention timepoint) varied across studies, as did the site of pain evaluated: PCI puncture site in the trial by Nilsson et al (2009) versus general pain in the trial by Bally et al (2003).…”
Section: Discussionmentioning
confidence: 99%